Christian-Muslim Relations in Indonesia: Five Challenges of the Twenty-First Century - Ibrahim Abu Rabi (Studia Islamika, 1998)
This paper - inspired by the "International Conference on Muslim-Christian Relations: Past, Present, and Future Dialogue and Cooperation", in Jakarta, August 1997 - discussed the challenges of Indonesia in relation to Christian-Muslim relations into the century 21.In August 1997, a major conference on Christian-Muslim relations and the challenges of religious plulalism in contemporary Indonesia was convenced at the Horison Hotel in Jakarta, Indonesia. DOI: 10.15408/sdi.v5i1.758